A long-term monitoring dataset of non-breeding waterbirds at Lake Miedwie, Poland (2002–2025) - Dominik Marchowski; Paweł Stańczak; Michał Jasiński; Sebastian Guentzel (Biodiversity Data Journal)
Lake Miedwie, located in north-western Poland, is one of the most important wetland areas for non-breeding waterbirds in the Central European region. Recognised as both an Important Bird Area (IBA) and part of the Natura 2000 network, the site supports large numbers of migratory and overwintering geese, ducks and other waterbirds. Since 2002, standardised surveys have been conducted during the non-breeding season to monitor population sizes and species composition. The site’s location on major flyways and its habitat diversity make it valuable for long-term ornithological monitoring.This dataset presents waterbird count data collected during the non-breeding season from 2002/2003 to 2024/2025, covering 23 seasons across 24 calendar years. The dataset includes 952 records of seasonal abundance for 14 waterbird species. The average total abundance was 7,933 (± 1,314 SE) individuals per season (mean of November, January and March), with a maximum of 36,095 in November 2002 and a minimum of 226 in March 2017. Trend analysis using the rtrim package in R indicated a moderate overall decline (λ = 0.976, 95% CI: [0.975 – 0.977]). Species-specific trends varied, with some taxa, such as Greylag Goose (Anser anser Linnaeus, 1758), increasing, while others, including Greater White-fronted Goose (Anser albifrons Scopoli, 1769), Eurasian Teal (Anas crecca Linnaeus, 1758) and Eurasian Coot (Fulica atra Linnaeus, 1758), declined. The dataset contributes valuable baseline data for wetland bird conservation, ecological assessment and future research in Central Europe. Importantly, such long-term monitoring also provides a robust reference point for assessing changes in climate and biodiversity over time.